Discussion of tumor mutation burden as an indicator to predict efficacy of immune checkpoint inhibitors: A case report - Wu, Mingrui; Liang, Lan; Dai, Xiaotian (Frontiers in Oncology, 2022)
There are many treatment options for advanced lung cancer, among which immunotherapy has developed rapidly and benefited a lot of patients. However, immunotherapy can only benefit a subgroup of patients, and how to select patients suitable for this therapy is critical. Tumor mutation burden (TMB) is one of the important reference indicators for immune checkpoint inhibitors (ICIs). But there are many factors influencing the usage of this indicator, which will lead to considerable consequences if not treating well. In this study, we adopted a clinical case as the basis to explore the value and significance of TMB. We hope that more predictive molecular markers will be discovered, which will bring more treatment methods for advanced lung cancer.